Identifying Empowerment Characteristics with Emphasis on Knowledge Management with Delphi Approach (Case Study: Kaleh Company) - Ziari, Atefeh; Kandelousi, Nader Sheikholeslami (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of identifying the characteristics of empowerment with emphasis on knowledge management with the Delphi approach (Case study: Kaleh Company). This research is applied in terms of purpose and descriptive-survey method. The statistical population of the research includes experts familiar with the issues of empowerment and knowledge management in Kaleh Company, 8 of whom have been selected to conduct the research. Hypotheses and test questions were analyzed based on the data obtained from the relevant questionnaires using Excel and EXPERT-CHOICE software. In this study, tests were performed through a checklist and localization of the questionnaire and measuring the opinion of experts to identify the components and then based on it as well as the combination of known factors with the opinions of experts to measure the factors. It is one of the most important strategies for empowering human resources in the organization. Developing training programs for employees and implementing short-term and long-term courses that increase the intellectual and professional abilities of employees is one of the factors that play a very important role in empowering employees. Training by providing the knowledge and skills needed to perform tasks efficiently and effectively, leads to a sense of self- confidence and self-worth in employees and as a result a sense of implementation of knowledge management in employees, which results in higher productivity in the organization. The results show that according to the results obtained in the third stage of Delphi, the average value obtained for all sub-criteria is more than 3.5, so the identified sub-criteria are approved.